Water resources and environment: education, training and research: conference proceedings - Colorado State University. Department of Civil Engineering, author; Colorado Water Resources Research Institute, author (Colorado State University. Libraries, 1992)
Proceedings of the Water Resources and Environment: Education, Training and Research Conference held on July 13-17, 1992 at Colorado State University in Fort Collins, Colorado.
Organized by Department of Civil Engineering and Colorado Water Resources Research Institute.
Keywords: Water resources development -- Study and teaching -- Colorado -- Congresses; Environmental protection -- Colorado -- Congresses